An audit of injuries in six english professional soccer academies - Read, P. J.; Oliver, J. L.; De Ste Croix, M. B. A.; Myer, G. D.; Lloyd, R. S. (Journal of Sports Sciences, 2018)
Regulations now state that professional academies in the United Kingdom are required to substantially increase the volume of soccer training. This study assessed the current injury occurrence, providing an update to reports published prior to the introduction of the Elite Player Performance Plan (EPPP). 608 soccer players aged 11-18 years from six professional soccer clubs were prospectively monitored, recording injuries during the 2014-2015 season. An injury rate of 1.32 injuries per player/season was indicated with a mean time loss of 21.9 days per injury. The greatest time loss per injury was in the U14s-U15s, and the highest rate of severe injuries in the U15s. Strains and sprains were the most common injury type, with the knee and ankle the most frequently injured anatomical sites. Seasonal variation indicated two peaks in injury incidence, occurring in September and January. In comparison to a published audit prior to the inception of the EPPP, this study indicates that academy soccer players are three-times more likely to experience an injury. Given that time loss and injury severity also increased during periods that typically follow rapid growth, these players should be considered an important group for training load monitoring and injury prevention strategies.